PERAN SOSIAL PEREMPUAN PERSPEKTIF AL-QUR’AN DAN HADIST - Zaenul Mahmudi (lp2m-uin malang, 2007)
Equality gender program designed by Indonesian government still has some obstacles. One of them is classical Islamic jurisprudence thoughts that discredited women roles in public sector and put them as second citizen. These thoughts, of course, agree with the social condition when they had been formulated. In order to actualize the understanding of al-Qur’an and Hadits in the need of nowdays society, we have to discover the meaning of Quranic verses and Hadits in the matter of social role of women in nowdays perspectives. This research uses library as a media for collecting data and the data collected had been analyzed by content dan discourse analysis. Quranic verses and Hadis that discredit women position in society must be understood in Arabian socio-cultural context when Muhammad received the messege (wahy). This research shows that men and women have the same chances and roles to occupy public duty in order to carry out “proposing good deeds and prohibiting misdeeds” (amr al-ma‘rûf wa nahy ‘an al-munkar) Keywords: Social role, Woman, Gender